Spherical Calcium Phosphate Nanoparticle Fillers Allow Polymer Processing of Bone Fixation Devices with High Bioactivity - Mohn, Dirk; Ege, Duygu; Feldman, Kirill; Schneider, Oliver D.; Imfeld, Thomas; Boccaccini, Aldo R.; Stark, Wendelin J. (Polymer Engineering and Science, 2010)
Treatment of bone defects generally requires a fixation device. Biodegradable implants can often prevent second operations in contrast to metallic implants that are surgically removed after healing. In this study, we investigate the preparation of a bone fixation device with additional bioactivity by adding nanoparticulate amorphous tricalcium phosphate (ATCP) to improve bonding to bone. Medically approved poly(lactideco-glycolide) (PLGA) and spherical (ATCP) nanoparticles were blended directly or through a two-step approach, where ATCP was first dispersed in PLGA by solvent casting, extruded and hot pressed producing blocks and bone screws. The latter route yielded good particle dispersion while blending alone led to inhomogeneous mixtures. Samples were immersed in simulated body fluid and showed rapid formation of surface hydroxyapatite layers (examined by X-ray diffraction and scanning electron microscopy) already after 3 days, thus confirming very high bioactivity. Polymer degradation during processing and upon simulated implantation conditions was followed by gel permeation chromatography. The elevated temperature during extrusion was the strongest single factor contributing to PLGA degradation. Screws could be machined out of extruded cylinders and demonstrated the ability to process PLGA/ATCP 90/10 composites with regular workshop tools. These properties suggest the use of such composites as improved, bioactive, and degradable bone fixation systems particularly in oral and maxillofacial surgery. © 2009 Society of Plastics Engineers.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.spheri